Nutritional Composition, Amino Acid Profiles, and Protein Digestibility of Indonesian Smoked Eel, Shirayaki, and Kabayaki - Budhiyanti, Siti Ari; Puspita, Indun Dewi; Ekantari, Nurfitri (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2025)
Eel (Anguilla sp.) is a catadromous fish with high nutritional value, originating in freshwater and migrating to spawn, producing glass eel larvae. In Indonesia, processed eel products such as kabayaki, shirayaki, and smoked eel, which are popular in Japan, have not been widely developed. Comprehensive data on the nutritional composition and protein quality of these products are essential for product development and nutritional improvement. This study aims to determine the nutritional composition, amino acid profiles, and in vitro protein digestibility of Indonesian smoked eel, shirayaki, and kabayaki. Analyses included nutritional composition, amino acid profiles using high-performance liquid chromatography (HPLC), and in vitro protein digestibility for processed eel products. The results indicated that the processing method affected the nutritional value, albumin, minerals, and amino acids. Fresh eel had the highest protein content, followed by smoked eel, while there was no significant difference between shirayaki and kabayaki. The protein digestibility was highest in smoked (67.59%), but there was no significant difference among the others (63.30-64.44%). Calcium (Ca), magnesium (Mg), and potassium (K) contents were highest in smoked eel compared to fresh eel and decreased significantly in shirayaki and kabayaki, but for zinc (Zn), shirayaki and kabayaki tend to be higher than smoked eel. An analysis of essential amino acids showed no significant difference between the processing methods. Leucine had the highest concentration, followed by valine, threonine, and isoleucine, with concentrations ranging from 4.02% to 7.83%. The research found that the best processing method was smoked, and there was no significant difference between kabayaki and shirayaki.